IL-17-Dependent Dysregulated Cutaneous Immune Homeostasis in the Absence of the Wiskott–Aldrich Syndrome Protein - Herman, Katherine E.; Yoshida, Takeshi; Hughson, Angela; Grier, Alex; Gill, Steven R.; Beck, Lisa A.; Fowell, Deborah J. (Frontiers in Immunology, 2022)
Wiskott-Aldrich Syndrome (WAS) is characterized by recurrent infections, thrombocytopenia, and eczema. Here, we show that WASp-deficient mice on a BALB/c background have dysregulated cutaneous immune homeostasis with increased leukocyte accumulation in the skin, 1 week after birth. Increased cutaneous inflammation was associated with epithelial abnormalities including altered keratinization, abnormal epidermal tight junctional morphology and increased trans-epidermal water loss; consistent with epidermal barrier dysfunction. Immune and physical barrier disruption was accompanied by progressive skin dysbiosis, highlighting the functional significance of the disrupted cutaneous homeostasis. Interestingly, the dysregulated immunity in the skin preceded the systemic elevation in IgE and lymphocytic infiltration of the colonic lamina propria associated with WASp deficiency. Mechanistically, the enhanced immune cell accumulation in the skin was lymphocyte dependent. Elevated levels of both Type 2 (IL-4, IL-5) and Type 17 (IL-17, IL-22, IL-23) cytokines were present in the skin, as well as the ‘itch’ factor IL-31. Unexpectedly, the canonical WAS-associated cytokine IL-4 did not play a role in the immune dysfunction. Instead, IL-17 was critical for skin immune infiltration and elevation of both Type 2 and Type 17 cytokines. Our findings reveal a previously unrecognized IL-17-dependent breakdown in immune homeostasis and cutaneous barrier integrity in the absence of WASp, targeting of which may provide new therapeutic possibilities for the treatment of skin pathologies in WAS patients.